Dinamika Ekonomi Surabaya Raya: Studi tentang Dampak PDRB Perkapita, Tingkat Kemiskinan, dan Upah Minimum terhadap Ketimpangan Pendapatan - Aisyah, Naflah Azmi Nur; Sishadiyati (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Based on data and publications published by the BPS, it is known that the Greater Surabaya area has a per capita GDP above the average per capita GDP of East Java, but the Gini Index value still shows a high position. This study evaluates the influence of per capita GDP, poverty rate, and minimum wage on income inequality in Greater Surabaya, utilizing secondary data from the Central Bureau of Statistics (BPS) for the period 2013-2023. The results show that Greater Surabaya has a higher GRDP per capita than the East Java average but records the highest Gini Index in Indonesia, signaling significant inequality. Analysis using the Common Effect Model panel data regression model reveals that the three variables simultaneously have a significant influence on income inequality. Specifically, GRDP per capita contributes positively to inequality, indicated by the significant difference between the industrial and service sectors compared to the low-wage sector. Meanwhile, poverty rate and minimum wage both affect inequality negatively, suggesting that effective income redistribution efforts and minimum wage increase policies by the government play a role in reducing income disparity.